INTEGRASI TEKNOLOGI AUGMENTED REALITY DALAM PEMBELAJARAN BAHASA ARAB UNTUK GEN Z - Nur Aini; Berliana Sari Harahap; Tengku Sinar Marwanda (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Generation Z in the field of education tends to be more interested in visual and audiovisual learning methods. Augmented Reality (AR) plays a significant role in the era of digitalization, especially in the education sector, including Arabic language learning. This study aims to explore the effectiveness of AR in improving Arabic language learning for Generation Z. The research employs a qualitative method and a literature study approach, involving the collection, evaluation, and analysis of written sources such as scientific journal articles, books, research reports, and other relevant documents related to the use of AR in Arabic language learning. The findings indicate that students who learn using AR experience a significant increase in motivation and comprehension of Arabic language material. This is because AR provides a learning experience that is more interactive, visual, and aligned with the characteristics of the digital generation. Thus, the integration of AR in Arabic language learning presents an innovative solution to address the challenges of education in the digital era and enhances the overall effectiveness of Arabic language teaching.